Mesangial cells are key contributors to the fibrotic damage seen in the lupus nephritis glomerulus - Rachael D. Wright; Paraskevi Dimou; Sarah J. Northey; Michael W. Beresford (BMC, 2019)
Abstract Background Lupus nephritis (LN) affects up to 80% of juvenile-onset systemic lupus erythematosus patients. Mesangial cells (MCs) comprise a third of the glomerular cells and are key contributors to fibrotic changes within the kidney. This project aims to identify the roles of MCs in an in vitro model of LN. Methods Conditionally immortalised MCs were treated with pro-inflammatory cytokines or with patient sera in an in vitro model of LN and assessed for their roles in inflammation and fibrosis. Results MCs were shown to produce pro-inflammatory cytokines in response to a model of the inflammatory environment in LN. Further the cells expressed increased levels of mRNA for extracellular matrix (ECM) proteins (COL1A1, COL1A2, COL4A1 and LAMB1), matrix metalloproteinase enzymes (MMP9) and tissue inhibitors of matrix metalloproteinases (TIMP1). Treatment of MCs with serum from patients with active LN was able to induce a similar, albeit milder phenotype. Treatment of MCs with cytokines or patient sera was able to induce secretion of TGF-β1, a known inducer of fibrotic changes. Inhibition of TGF-β1 actions through SB-431542 (an activin A receptor type II-like kinase (ALK5) inhibitor) was able to reduce these responses suggesting that the release of TGF-β1 plays a role in these changes. Conclusions MCs contribute to the inflammatory environment in LN by producing cytokines involved in leukocyte recruitment, activation and maturation. Further the cells remodel the ECM via protein deposition and enzymatic degradation. This occurs through the actions of TGF-β1 on its receptor, ALK5. This may represent a potential therapeutic target for treatment of LN-associated fibrosis.